2016
DOI: 10.1002/sej.1237
|View full text |Cite
|
Sign up to set email alerts
|

If we can't have it, then no one should: Shutting Down Versus Selling in Family Business Portfolios

Abstract: Research summary How does a business family manage its business portfolio in times of declining performance to sustain the portfolio's long‐term endurance? Drawing on social identity theory and six family business portfolios from Pakistan, we find that business families may prefer to shut down a satellite business rather than sell it, which is primarily driven by identity considerations. In addition, the family's goal to recycle the assets, the aim to restart the business later, and the increasing decline in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 126 publications
(190 reference statements)
2
71
2
Order By: Relevance
“…As such, more dynamic theorizing should consider entrepreneurial and stakeholder motives. As indicated by studies investigating the moderators of the relationships in different venture phases (e.g., Akhter et al, ; George et al, ; Gregoire & Shepherd, ; Khan et al, ), the effects of motivation differ depending on context. This perspective can be applied in future research to clarify how path dependencies or key stakeholder concerns might impact motives both as antecedents as well as moderators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, more dynamic theorizing should consider entrepreneurial and stakeholder motives. As indicated by studies investigating the moderators of the relationships in different venture phases (e.g., Akhter et al, ; George et al, ; Gregoire & Shepherd, ; Khan et al, ), the effects of motivation differ depending on context. This perspective can be applied in future research to clarify how path dependencies or key stakeholder concerns might impact motives both as antecedents as well as moderators.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this multidimensional approach to studying venture exits, scholars have investigated the motivational forces involved in family business decisions of whether to exit via selling versus shutting down (Akhter et al, ). Interestingly, the primary motivation to sell, as opposed to shut down, is the identity fit between the family and the venture—the greater the alignment between the identity of the family and the venture, the more likely operations will be shut down instead of sold to an outsider (see also Moen et al, ).…”
Section: Entrepreneurial Motivation and Venture Exitmentioning
confidence: 99%
“…Doing so reduces estate taxes and has the appearance of perpetuating one's entrepreneurial legacy but often reduces the vitality and value of the enterprise (Zellweger & Kammerlander, 2015). Akhter, Sieger, and Chirico (2016) also document cases in which owner-managers closed their firms, rather than sell, because their firms would simply not be the same without them.…”
Section: Transfer Rights and Succession Hazardsmentioning
confidence: 99%
“…By entrepreneurial activities instead, inspired by Nordqvist and Melin (2010), we refer to entrepreneurial entry and exit. Only four papers considered entrepreneurial exit (Akhter, Sieger, and Chirico 2016;Dehlen et al 2014;Salvato, Chirico, and Sharma 2010;Wennberg et al 2011), and the majority focused on entrepreneurial entry. Entrepreneurial entry, in the context of an existing firm, is generally known as corporate entrepreneurship (CE).…”
Section: Entrepreneurship In Family Firmsmentioning
confidence: 99%
“…They suggested that this relationship was moderated by the dissimilarity of identity conflict in the past, and that the moderation was stronger in family firms with low identity negotiation ability. In line with Shepherd andHaynie (2009), Akhter, Sieger, andChirico (2016) considered the decision to shut down the business as an entrepreneurial act, and theorized about the existence of a positive relationship between identity fit (between owning family and satellite business) and the likelihood of shutting down versus selling the satellite business. The concept of familyto-firm unity is similar.…”
Section: Family Business Status As a Determinant Of Entrepreneurshipmentioning
confidence: 99%